Productos forestales no maderables de origen vegetal en cuatro comunidades rurales de la parroquia el tambo, cantón catamayo, provincia de Loja - Contento Yunga, Cristian Geovanny (2021)
Non-timber forest products (NTFPs) are of great importance to the development of rural communities' livelihoods in Ecuador; however, the lack of knowledge and the devaluation of current generations cause the loss of knowledge and use of plant species that provide NTFPs; In response to this problem, this research aims to identify the plant species that provide NTFP, to know their current, traditional and cultural uses and to propose alternative management techniques for NTFP species in the communities of Bellavista, La Argentina, Las Achiras and San Antonio de Paycapamba in the parish of El Tambo, Catamayo. To compile information on NTFP use of plant species, 386 surveys were conducted in three age groups: 15 to 30 years old, 31 to 50 years old and over 50 years old. The information obtained was used to calculate the value of use, frequency of use and the level of significant use of the species reported by the communities; based on this information, a SWOT analysis was carried out in order to provide management alternatives for the species studied. The use of 126 species was recorded, included in 111 genera and 64 families including trees, shrubs, vines and herbs. The plant species with the highest use value were Hesperomeles obtusifolia and Oreocallis grandiflora, which are used in five use categories each. The human medicine category recorded the highest number of species, 56 in total. Ten species of importance and cultural value were recorded for the study area that reached a level of significant use (NUS) equal to or higher than 20%, where Laurus nobilis, Oreocallis grandiflora and Cinchona officinalis stand out. The knowledge of NTFP use and exploitation in men and women is similar, with a slight superiority in men; in addition, there is evidence of the loss of knowledge of the use of species in the new generations, being the age group older than 50 years who still know and use the plants in a traditional way. With the results obtained from the first objective, sustainable management alternatives for NTFP species were proposed to contribute to the conservation of biological and cultural diversity of the local population. Key words: NTFP, biological and cultural diversity, ancestral knowledge, ethno botany.